9-05: Both Selective And Non-Selective His Pacing Preserve Left Ventricle Activation. (10th June 2016) - Arnold, Ahran; Shun-Shin, Matthew; Keene, Daniel; Sohaib, Afzal; Finegold, Judith; Lefroy, David; Davies, Wyn; Lim, Phang Boon; Kanagaratnam, Prapa; Koa-Wing, Michael; Linton, Nicholas; Peters, Nicholas S.; et al.
Abstract: Purpose: His pacing provides physiological pacing by preserving ventricular activation via the His-Purkinjie system. The characteristics of selective and non-selective His capture have not been well established. Methods: The CardioInsight ECVUE(TM) system uses a 252-electrode vest to non-invasively map epicardial electrical activity from the entire myocardium in single beat. Vests were applied to four patients with heart failure undergoing His pacing. Mapping of ventricular activation was performed during selective and non-selective His pacing (as determined by the 12 lead surface ECG and intra-cardiac His signal) as well as during intrinsic ventricular activation. Results: Non-Selective His pacing resulted in early activation in the mid and basal right ventricle (RV), but subsequent RV activation matched that occurring during intrinsic activation. The epicardial ventricular activation pattern of selective His pacing was the same as activation observed during un-paced sinus rhythm. The left ventricular activation pattern observed with non-selective His pacing was identical to that seen during selective His pacing and intrinsic activation. Figure 1 depicts the activation maps derived from one patient with ischaemic cardiomyopathy (Ejection Fraction 35%) with a prolonged PR interval of 280ms but a normal QRS duration of 114ms. Left ventricular total activation time (LVTAT) did not differ significantly with non-selective His pacing compared to selective His pacing or intrinsic activation, mean change in LVTAT -0.8ms and -8ms, respectively, p = 0.8 & 0.4 in paired t-tests. Conclusions: Non-selective His pacing produces early activation of the right ventricle, reflecting local myocardial capture. However, importantly, LV activation appears to occur via the His-Purkinjie system and therefore would not be expected to produce the negative effect on left ventricular function, which can be observed with conventional RV pacing. Non-selective His capture has the advantage that ventricular capture is maintained even if infra-hissian block develops or direct His capture is lost.